Characterization of chalcogen bonding interactions via an in‐depth conceptual quantum chemical analysis. Issue 10 (10th November 2017) - De Vleeschouwer, Freija; Denayer, Mats; Pinter, Balazs; Geerlings, Paul; De Proft, Frank
Abstract : The chalcogen bond has been acknowledged as an influential noncovalent interaction (NCI) between an electron‐deficient chalcogen (donor) and a Lewis base (acceptor). This work explores the main features of chalcogen bonding through a large‐scale computational study on a series of donors and acceptors spanning a wide range in strength and character of this type of bond: (benzo)chalcogenadiazoles (with Ch = Te/Se/S) versus halides and neutral Lewis bases with O, N, and C as donor atoms. We start from Pearson's hard and soft acids and bases (HSAB) principle, where the hard nature of the chalcogen bond is quantified through the molecular electrostatic potential and the soft nature through the Fukui function. The σ‐holes are more pronounced when going down in the periodic table and their directionality matches the structural orientation of donors and acceptors in the complexes. The Fukui functions point toward an n→σ*‐type interaction. The initial conjectures are further scrutinized using quantum mechanical methods, mostly relating to the systems' electron density. A Ziegler–Rauk energy decomposition analysis shows that electrostatics plays a distinctly larger role for the soft halides than for the hard, uncharged acceptors, associated with the softness matching within the HSAB principle. The natural orbital for chemical valence analysis confirms the n→σ* electron donation mechanism. Finally, the electron density and local density energy at the bond critical point in the quantum theory of atoms in molecules study and the position of the spikes in the reduced density gradient versus density plot in the NCI theory situate the chalcogen bond in the same range as strong hydrogen bonds. © 2017 Wiley Periodicals, Inc. Abstract : This work explores the main features of chalcogen bonding through a large‐scale computational study on an extensive and relevant series of donors and acceptors. The hard and soft acids and bases principle forms the basis, evaluated by the molecular electrostatic potential (MEP) probing the hard–hard interactions and the Fukui functions probing the soft–soft interactions between the chalcogen‐bond donors and acceptors (see Figure: MEP plotted on Fukui function surface).